ANALISIS HUKUM ISLAM TERHADAP POLA KEMITRAAN USAHA PETERNAKAN AYAM POTONG DI PANCA RIJANG SIDRAP - Masluha; Hamid, Abdul; Aris (DIKTUM: Jurnal Syariah dan Hukum, 2019)
Partnership Pattern is a partnership or what is known as syirkah, which is a collaboration between two parties, namely between the Company (Core) and breeders (Plasma). Through this partnership, both parties benefit, the farmers get capital while the company benefits from marketing livestock production and production facilities. The partnership pattern between PT. Ciomas Adistwa with breeders in the poultry farm business in Panca Rijang Sidrap revealed: first, the company facilitated the needs of farmers in terms of availability of production facilities and livestock products, while breeders prepared land, cages and cage equipment in the form of eating places, drinking places, and labor. Second, the contract between PT.Ciomas Adisatwa and the breeders in Panca Rijang Sidrap made a contract in accordance with an agreement agreed between each party. Third, the view of the Islamic economy towards the implementation of the business of broiler breeders in Panca Rijang Sidrap with the company PT.Ciomas Adisatwa, namely in terms of generating profits which are permitted according to Islam with the principle of mutual help to help in the good.